The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ijms21228849
|View full text |Cite
|
Sign up to set email alerts
|

The Antipsychotic D2AAK1 as a Memory Enhancer for Treatment of Mental and Neurodegenerative Diseases

Abstract: The treatment of memory impairments associated with the central nervous system diseases remains an unmet medical need with social and economic implications. Here we show, that a multi-target ligand of aminergic G protein-coupled receptors with antipsychotic activity in vivo (D2AAK1) stimulates neuron growth and survival and promotes neuron integrity. We focused on the multilevel evaluation of the D2AAK1-related effects on neurons in terms of behavioral, cellular, molecular, and biochemical features in vivo and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 62 publications
(72 reference statements)
0
8
0
Order By: Relevance
“…Previously, we provided evidence of the unique properties of the lead structure D2AAK1 in terms of neuronal growth stimulation and cell survival promotion. The events observed were related to the up-regulation of neurotrophic factors, CAMKI kinase and mechanisms related to cell proliferation confirmed by BrdU incorporation into newly synthesized DNA [ 8 ]. Moreover, D2AAK1 showed antioxidant properties, decreased the levels of ROS and RNS and prevented excitotoxicity by decreasing intracellular calcium and NMDA levels.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, we provided evidence of the unique properties of the lead structure D2AAK1 in terms of neuronal growth stimulation and cell survival promotion. The events observed were related to the up-regulation of neurotrophic factors, CAMKI kinase and mechanisms related to cell proliferation confirmed by BrdU incorporation into newly synthesized DNA [ 8 ]. Moreover, D2AAK1 showed antioxidant properties, decreased the levels of ROS and RNS and prevented excitotoxicity by decreasing intracellular calcium and NMDA levels.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing the proliferation of neurons and creating new neural connections is a key point in the treatment of neurodegenerative and mental diseases [ 2 ]. Upon analyzing the structure–proliferation relationship of the tested compounds, it can be clearly stated that the lead structure of D2AAK1 causes the highest increase in proliferation [ 8 ] compared to its derivatives. The increase in proliferation can be induced as a result of the activation of mechanisms related to the hormesis effect.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compound 2 (D2AAK1) was selected as the most promising compound from this VS study (Figure 3). Additional in silico, in vitro and in vivo studies confirmed that D2AAK1 is a multi-target ligand of aminergic GPCRs, with neuroprotective properties and pro-cognitive activity, therefore providing a new therapeutic option for the treatment of multifactorial brain disorders (92)(93)(94). Since in vitro studies showed the affinity of D2AAK1 for dopamine D1 and D3 receptors, as well as for serotonin 5-HT1A and 5-HT2A receptors, molecular dynamics (using Desmond) and molecular docking (using GLIDE) studies were used to reveal its interactions and binding poses with these targets at the molecular level.…”
Section: Successful Application Of Cadd Approaches In the Discovery Of Aminergic Gpcr Ligands For Treatment Of Neuropsychiatric Disordersmentioning
confidence: 92%